Bank levy as a tool of internalisation of externalities generated by banks: Analysis of the domestic banks’ response to the introduced tax (Economic and Political Thought, 2018)
The main aim of this article is to present the possibility of internalisationof negative externalities generated by banks with the use of a banklevy introduced in Poland at the beginning of 2016. The conducted surveytakes into account Polish banks’ adaptive response to newly implementedtax (tax optimisation) and co-effects of the group response materialised inlocal interbank and sovereign debt markets. Empirical assessment of the banklevy introduction and evaluation of its externalities internalisation potentialis based on statistical data gathered in 2015–2017.
Keywords: negative externalities internalisation, bank levy, tax optimisation